Laboratory evidence for the formation of hydrogenated fullerene molecules. Issue Volume 15:Issue S350(2019) (April 2019) - Thrower, J. D.; Pantazidis, G.; Scheffler, M.; Simonsen, F. D. S.; Jensen, P. A.; Hornekær, L.
Abstract: Experimental evidence for the formation of hydrogenated fullerene molecules is presented. Films of C60 were grown on a highly oriented pyrolytic graphite (substrate) and exposed to a beam of deuterium atoms. Thermal desorption combined with mass spectrometry was used to determine the deuterated fullerene products formed, revealing a maximum degree of deuteration corresponding to C60 D36 . Release of D2 from the deuterated C60 film occurs at a much higher temperature than for D-saturated graphite.